Analisis Dinamika dan Tantangan Perkembangan Sistem Moneter Internasional Pada Ekonomi Global - Laeladzul Kongidah; Risma Afni Zakiah; Sarpini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This article discusses the international monetary system as a crucial element in maintaining global economic stability, regulating currency exchange rates, capital flows, and international trade. The system continues to face various challenges, such as exchange rate fluctuations, the impact of financial digitalization, and the threat of financial crises that could disrupt global equilibrium. This research aims to provide a deeper understanding of the dynamics of the international monetary system, which has evolved from the gold standard to the floating exchange rate system. The literature review reveals the significant role of international institutions like the IMF and the World Bank in coordinating monetary policies between countries to ensure global stability. The analysis results suggest that the international monetary system requires continuous reform, especially in addressing the challenges of digitalization and trade fragmentation. This article contributes to the development of knowledge by offering new perspectives on strengthening the international monetary system through technological innovation and international collaboration.